A prospective examination of COVID‐19‐related social distancing practices on suicidal ideation. Issue 5 (29th June 2021) - Ammerman, Brooke A.; Burke, Taylor A.; McClure, Kenneth; Jacobucci, Ross; Liu, Richard T.
Abstract: Background: The COVID‐19 pandemic has spurred the implementation of several public safety measures to contain virus spread, most notably socially distancing policies. Prior research has linked similar public safety measures (i.e., quarantine) with suicide risk, in addition to supporting the role of social connection in suicidal thoughts and behaviors; consequently, there is a need to better understand the relationship between widespread social distancing policies and suicide risk. The current study aimed to examine the prospective association between COVID‐19‐related social distancing practices and suicidal ideation. Methods: Participants (N = 472) completed measures of suicidal ideation and impacts of social distancing practices at baseline and two weeks later. Results: After controlling for general psychosocial distress (i.e., depression, social connectedness), cross‐lagged regression models identified prospective, bidirectional relationships between perceived impacts of social distancing on one's mental health and both passive and active suicidal ideation. The impact of social distancing on work/social routine was not associated with suicidal ideation. Conclusions: Overall, findings suggest the importance of an individual's perception regarding the effect of social distancing on their mental health, rather than the disruption to work or social routine, in suicide risk. Findings highlight potential targets for suicide risk prevention and intervention.